A low-temperature curing silver chloride paste and its preparation method and application

Through the technology of curing silver chloride paste at low temperature, the problem of shrinkage and deformation of the PU conductive film during the high-temperature curing of medical electrode sheets is solved, and the excellent conductivity and service life of the electrode sheets are achieved.

CN116895397BActive Publication Date: 2025-03-04GUANGDONG NANHAI ETETB TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310933931.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-03-04
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

The existing medical electrode sheets cause shrinkage and deformation of the PU conductive film during high-temperature curing, affecting the conductive performance and service life.

Method used

The silver chloride paste is cured with low temperature. By preparing a resin system of polyester resin, polyurethane resin and epoxy resin, combining a silver powder system of sheet-shaped silver powder, spherical silver powder and silver chloride powder, and using two solvents with different boiling points, the silver chloride paste is cured at low temperature below 90°C.

Benefits of technology

The shrinkage and deformation of the PU conductive film is avoided, and the excellent contact conductivity of the electrode sheet is ensured and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004363029260000121
    Figure BDA0004363029260000121
Patent Text Reader

Abstract

The present invention discloses a low-temperature curing silver chloride paste and a preparation method and application thereof. The low-temperature curing silver chloride paste comprises 5 to 30 parts of a matrix resin, 40 to 90 parts of a conductive silver powder and 5 to 30 parts of a combined solvent, calculated by weight. The matrix resin comprises a polyester resin, a polyurethane resin and an epoxy resin. The conductive silver powder comprises flaky silver powder, spherical silver powder and silver chloride powder. The average flake diameter of the flaky silver powder is 2 to 5 μm, and the particle diameter of the spherical silver powder is 200 to 500 nm. The combined solvent comprises a first solvent and a second solvent. The boiling point of the first solvent is ≥180°C, the boiling point of the second solvent is ≥100°C, and the boiling point of the second solvent is <180°C. The low-temperature curing silver chloride paste and the preparation method thereof proposed in this scheme improve the formula of the silver chloride paste so as to achieve low-temperature rapid curing at 90°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive paste, and in particular to a low-temperature curing silver chloride paste and a preparation method and application thereof. Background Art

[0002] Flexible wearable ECG sensor electrodes sense bioelectric signals through intact skin to achieve ECG diagnosis and ECG monitoring. They replace ordinary ECG suction cups and electrode clips and can be used to detect human ECG for a long time. Compared with ordinary suction cups, the electrode sheets are soft and sticky, and can be stably and fixedly attached to the corresponding skin parts of the human body. They will not fall off due to changes in patient position, activities, sweating, etc. They can help doctors record the patient's various ECG activities in a timely and accurate manner, help doctors detect changes in the patient's condition early, and monitor the patient's vital signs. Therefore, they are widely used in clinical work.

[0003] Silver chloride has good conductivity and biocompatibility, and can be safely used for electrical stimulation of the skin surface and detection of bioelectric signals. Therefore, silver chloride electrodes are very suitable for applications such as medical electrophysiology and bioelectric signal detection.

[0004] However, the currently commonly used medical electrode sheet is a silver chloride conductive paste printed on a PU conductive film with good flexibility, and the substrate of the PU conductive film is a polyurethane (PU)-based film material, which has poor heat resistance and is prone to shrinkage and deformation when the temperature is greater than 100°C. On the one hand, it is not conducive to the construction of subsequent printing processes during the electrode sheet production process, and on the other hand, the shrinkage of the PU conductive film will also have an adverse effect on the conductive performance and aging resistance of the electrode sheet. The general silver chloride conductive paste has a curing temperature of 120 to 150°C, which can easily cause the PU conductive film to shrink and deform during the production process, which is not conducive to ensuring that the existing medical electrode sheet has good conductive properties, nor is it conducive to extending its service life. Summary of the invention

[0005] The purpose of the present invention is to provide a low-temperature curing silver chloride paste and a preparation method thereof, and to improve the formula of the silver chloride paste so that the silver chloride paste can be quickly cured at a low temperature of 90°C.

[0006] Another object of the present invention is to propose a medical electrode sheet using the above-mentioned low-temperature curing silver chloride paste, which is beneficial to avoid shrinkage and deformation of the PU conductive film matched with the silver chloride paste, and ensure that the medical electrode sheet using the silver chloride paste has excellent contact conductivity, so as to overcome the shortcomings of the prior art.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A low-temperature curing silver chloride paste, calculated by weight, comprises 5 to 30 parts of a base resin, 40 to 90 parts of a conductive silver powder and 5 to 30 parts of a combined solvent;

[0009] The matrix resin includes polyester resin, polyurethane resin and epoxy resin;

[0010] The conductive silver powder includes flaky silver powder, spherical silver powder and silver chloride powder, the average flake diameter of the flaky silver powder is 2-5 μm, and the particle diameter of the spherical silver powder is 200-500 nm;

[0011] The combined solvent includes a first solvent and a second solvent, the boiling point of the first solvent is ≥180°C, the boiling point of the second solvent is ≥100°C, and the boiling point of the second solvent is <180°C.

[0012] Preferably, calculated by weight, the matrix resin includes 30 to 50 parts of polyester resin, 40 to 60 parts of polyurethane resin and 1 to 10 parts of epoxy resin.

[0013] Preferably, the glass transition temperature of the polyester resin is ≥70°C.

[0014] Preferably, the elongation at break of the polyurethane resin is ≥700%.

[0015] Preferably, calculated by weight, the conductive silver powder includes 40 to 70 parts of flaky silver powder, 5 to 20 parts of spherical silver powder and 10 to 40 parts of silver chloride powder.

[0016] Preferably, the particle size of the silver chloride powder is 1 to 2 μm.

[0017] Preferably, the boiling point of the first solvent includes any one or more combinations of dibasic acid esters, diethylene glycol butyl ether acetate, isophorone and diethylene glycol ethyl ether acetate;

[0018] The boiling point of the second solvent includes any one or more combinations of methyl isobutyl ketone, n-butyl acetate and ethylene glycol ethyl ether acetate.

[0019] A method for preparing a low-temperature curing silver chloride paste, which is used for the above-mentioned low-temperature curing silver chloride paste, comprises the following steps:

[0020] A. Mixing a formulated amount of base resin and a part of a formulated amount of a combined solvent, heating and dissolving, to obtain a carrier;

[0021] B. Mixing the carrier, the formulated amount of conductive silver powder and the remaining formulated amount of the combined solvent, and stirring at a low speed to obtain a pre-made slurry;

[0022] C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

[0023] Preferably, in step A, the dissolution temperature of the heating and dissolving step is 80 to 120° C., and the dissolution time is 6 to 12 hours;

[0024] In step B, the stirring speed of the low-speed stirring step is 50 to 500 rpm, and the stirring time is 30 to 120 min.

[0025] A medical electrode sheet uses the above-mentioned low-temperature curing silver chloride paste, including a PU conductive film and a conductive layer, wherein the conductive layer is arranged on the top of the PU conductive film, and the conductive layer is cured by the low-temperature curing silver chloride paste, the curing temperature of the low-temperature curing silver chloride paste is ≤90°C, and the curing temperature of the low-temperature curing silver chloride paste is ≤5min.

[0026] The technical solution provided by the embodiments of the present application may have the following beneficial effects:

[0027] 1. A resin system of silver chloride paste is formed by compounding polyester resin, polyurethane resin and epoxy resin. Among them, polyester resin can effectively give silver chloride paste the ability to dry quickly and at low temperature to achieve the effect of rapid low-temperature curing, and it can also ensure a certain flexibility for the cured silver chloride paste. Polyurethane resin can effectively give silver chloride paste flexibility on the substrate film to extend the service life of the electrode sheet using silver chloride paste. Epoxy resin can effectively improve the adhesion of silver chloride paste on the substrate film, and after compounding with polyester resin and polyurethane resin, the adhesion of silver chloride paste can be greatly improved.

[0028] 2. A silver powder system of silver chloride paste is formed by compounding flaky silver powder, spherical silver powder and silver chloride powder. Among them, micron-scale flaky silver powder can form a microscopically undulating three-dimensional structure by overlapping or arranging, thereby improving the conductivity and reducing the resistivity. Compared with flaky silver powder, the surface area of ​​nano-scale spherical silver powder is relatively small, so the conductivity and reflectivity of spherical silver powder are relatively low. However, since spherical silver powder has better fluidity and filling properties, it can fill the small space left after the flaky silver powder and silver chloride powder are overlapped, making the distribution of conductive silver powder in the silver chloride paste layer more compact, thereby effectively improving the aging resistance of the electrode sheet using it. Finally, adding an appropriate amount of silver chloride powder to the silver powder system can increase the concentration of chloride ions in the silver chloride paste, thereby accelerating the rate of silver ion reduction, and further improving the conductivity and reducing the resistivity; and the silver chloride powder has excellent corrosion resistance. In a medical environment, the electrode may come into contact with various substances, such as body fluids, drugs, etc., which may corrode the electrode. The corrosion resistance of the silver chloride powder can protect the long-term use of the electrode, thereby further extending the service life of the electrode.

[0029] 3. Use two solvents with different boiling points to compound and form a solvent system for silver chloride paste. The solvent system and the resin system in this case work together to further achieve low-temperature rapid curing of the paste while ensuring the performance of the paste. DETAILED DESCRIPTION

[0030] A low-temperature curing silver chloride paste, calculated by weight, comprises 5 to 30 parts of a base resin, 40 to 90 parts of a conductive silver powder and 5 to 30 parts of a combined solvent;

[0031] The matrix resin includes polyester resin, polyurethane resin and epoxy resin;

[0032] The conductive silver powder includes flaky silver powder, spherical silver powder and silver chloride powder, the average flake diameter of the flaky silver powder is 2-5 μm, and the particle diameter of the spherical silver powder is 200-500 nm;

[0033] The combined solvent includes a first solvent and a second solvent, the boiling point of the first solvent is ≥180°C, the boiling point of the second solvent is ≥100°C, and the boiling point of the second solvent is <180°C.

[0034] In order to reduce the curing temperature of silver chloride paste, this scheme proposes a low-temperature curing silver chloride paste, including 5 to 30 parts of a base resin, 40 to 90 parts of a conductive silver powder and 5 to 30 parts of a combined solvent, wherein the base resin is used as a binder for the conductive silver powder so as to fix the conductive silver powder on a substrate during application, and the combined solvent is used to dilute and adjust the viscosity of the silver chloride paste so that it is easy to process and coat on a substrate.

[0035] First, this scheme uses polyester resin, polyurethane resin and epoxy resin to compound to form a resin system of silver chloride paste. Among them, polyester resin can effectively give silver chloride paste the ability to dry quickly and at low temperature to achieve the effect of rapid low-temperature curing, and it can also ensure a certain flexibility for the cured silver chloride paste. Polyurethane resin can effectively give silver chloride paste flexibility on the substrate film, so as to extend the service life of the electrode sheet using silver chloride paste. Epoxy resin can effectively improve the adhesion of silver chloride paste on the substrate film, and after compounding with polyester resin and polyurethane resin, the adhesion of silver chloride paste can be greatly improved.

[0036] Then, in order to improve the printing performance of silver chloride paste while ensuring the conductive performance of silver chloride paste, so as to improve the adhesion and service life of the electrode sheet using it, this scheme also uses flaky silver powder, spherical silver powder and silver chloride powder to compound to form a silver powder system of silver chloride paste. Among them, the micron-scale flaky silver powder can form a microscopic undulating three-dimensional structure by superposition or arrangement, thereby improving the conductive performance and reducing the resistivity. Compared with flaky silver powder, the surface area of ​​nano-scale spherical silver powder is relatively small, so the conductive performance and reflectivity of spherical silver powder are relatively low, but because spherical silver powder has better fluidity and filling properties, it can fill the small space left after the flaky silver powder and silver chloride powder are overlapped, so that the distribution of conductive silver powder in the silver chloride paste layer is more compact, thereby effectively improving the aging resistance of the electrode sheet using it. Finally, adding an appropriate amount of silver chloride powder to the silver powder system can increase the concentration of chloride ions in the silver chloride paste, thereby accelerating the rate of silver ion reduction, and further improving the conductivity and reducing the resistivity; and the silver chloride powder has excellent corrosion resistance. In a medical environment, the electrode may come into contact with various substances, such as body fluids, drugs, etc., which may corrode the electrode. The corrosion resistance of the silver chloride powder can protect the long-term use of the electrode, thereby further extending the service life of the electrode.

[0037] In addition, this scheme also limits the average flake diameter of flaky silver powder and the particle size of spherical silver powder. If the average flake diameter of flaky silver powder is too small, it is easy to make the overlap between the silver powder system loose, thereby reducing the conductivity of the silver paste; if the average flake diameter of flaky silver powder is too large, it is easy to form voids, resulting in an uneven surface of the silver paste layer, which will also affect its conductivity. If the particle size of the spherical silver powder is too large, it is not conducive to improving the conductivity of the silver paste, and if the particle size of the spherical silver powder is too small, it is easy to cause the thixotropy of the silver paste to be too large.

[0038] Finally, in order to further reduce the curing temperature of silver chloride paste and increase the curing speed of silver chloride paste, this solution also uses two solvents with different boiling points to form a solvent system for silver chloride paste. The synergistic effect of the solvent system and the resin system in this case can further achieve low-temperature rapid curing of the paste while ensuring the performance of the paste.

[0039] To further illustrate, calculated by weight, the base resin includes 30 to 50 parts of polyester resin, 40 to 60 parts of polyurethane resin and 1 to 10 parts of epoxy resin.

[0040] In order to further ensure the performance of the silver chloride paste, this solution optimizes the addition ratio of polyester resin, polyurethane resin and epoxy resin in the matrix resin.

[0041] When the polyester resin content is too high, the bending performance of the silver chloride paste after curing is poor, which makes it difficult to meet the flexibility requirements of the electrode sheet. When the polyester resin content is too low, the silver chloride paste is difficult to meet the demand for rapid curing at low temperatures.

[0042] The addition of polyurethane resin will affect the hardness of the silver chloride paste after curing. In order to take into account both the flexibility and hardness of the silver chloride paste after curing, this scheme preferably adds 40 to 60 parts of polyurethane resin; if the content of polyurethane resin is too high, the hardness of the silver chloride paste after curing at low temperature is low, and it is easy to wear and cause the electrode sheet to fail; if the content of polyurethane resin is too low, the bending performance of the silver chloride paste is difficult to meet the standard.

[0043] Although epoxy resin can give the paste better adhesion, if the silver chloride paste contains too much epoxy resin, it will affect the conductive properties of the paste system and weaken the contact conductivity of the silver chloride paste. Therefore, in this scheme, the addition amount of epoxy resin is preferably 1 to 10 parts.

[0044] It is further specified that the glass transition temperature of the polyester resin is ≥70°C.

[0045] The glass transition temperature refers to the temperature corresponding to the transition from the glass state to the highly elastic state. In order to further ensure the curing and construction performance of the silver chloride paste, this solution further optimizes the glass transition temperature of the polyester resin. If the glass transition temperature of the polyester resin is too high, on the one hand, the drying speed of the silver chloride paste will be reduced, and on the other hand, its stability will be lacking at a higher ambient temperature.

[0046] It is further specified that the elongation at break of the polyurethane resin is ≥ 700%.

[0047] In order to further ensure that the silver chloride paste has good flexibility, the present solution preferably sets the elongation at break of the polyurethane resin to ≥700%, so that when the cured silver chloride paste is subjected to a bending test after being combined with the polyester resin, the resistance change rate after folding 10 times is ≤300%.

[0048] To further illustrate, calculated by weight, the conductive silver powder includes 40 to 70 parts of flaky silver powder, 5 to 20 parts of spherical silver powder and 10 to 40 parts of silver chloride powder.

[0049] Since the flaky silver powder overlaps in the silver powder system to form a three-dimensional structure with microscopic undulations, in order to ensure its conductive properties, the lower limit of its addition amount is preferably 40 parts in this case. In addition, since an excessively high content of flaky silver powder can easily reduce the corrosion resistance of the silver paste, the upper limit of its addition amount is preferably 70 parts in this case.

[0050] In addition, in order to improve the construction performance of silver chloride paste while ensuring conductivity, the addition amount of spherical silver powder in this case is preferably 5 to 20 parts. If the addition amount of spherical silver powder in the silver powder system is too high, it is easy to cause the viscosity of the silver paste to increase, the thixotropy to increase, and the printability to deteriorate.

[0051] Finally, in order to take into account both the conductivity and corrosion resistance of silver chloride powder, the addition amount of silver chloride powder is preferably 10 to 40 parts in this case.

[0052] To further illustrate, the particle size of the silver chloride powder is 1-2 μm.

[0053] In one embodiment of the present technical solution, the particle size of the silver chloride powder is preferably 1-2 μm to ensure the compactness of the silver chloride paste, thereby ensuring its conductive performance.

[0054] Further, the boiling point of the first solvent includes any one or more combinations of dibasic acid esters, diethylene glycol butyl ether acetate, isophorone and diethylene glycol ethyl ether acetate;

[0055] The boiling point of the second solvent includes any one or more combinations of methyl isobutyl ketone, n-butyl acetate and ethylene glycol ethyl ether acetate.

[0056] It should be noted that the divalent acid ester used in this case, namely DBE, was purchased from DuPont Company of the United States.

[0057] A method for preparing a low-temperature curing silver chloride paste, which is used to prepare the above-mentioned low-temperature curing silver chloride paste, comprises the following steps:

[0058] A. Mixing a formulated amount of base resin and a part of a formulated amount of a combined solvent, heating and dissolving, to obtain a carrier;

[0059] B. Mixing the carrier, the formulated amount of conductive silver powder and the remaining formulated amount of the combined solvent, and stirring at a low speed to obtain a pre-made slurry;

[0060] C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

[0061] Further, in step A, the dissolution temperature of the heating and dissolving step is 80 to 120° C., and the dissolution time is 6 to 12 hours;

[0062] In step B, the stirring speed of the low-speed stirring step is 50 to 500 rpm, and the stirring time is 30 to 120 min.

[0063] This scheme also proposes a preparation method of the above-mentioned low-temperature curing silver chloride paste, which has simple steps and strong operability, can effectively ensure that the silver chloride paste is fully dispersed, and at the same time ensure that its paste performance is not weakened.

[0064] A medical electrode sheet uses the above-mentioned low-temperature curing silver chloride paste, including a PU conductive film and a conductive layer, wherein the conductive layer is arranged on the top of the PU conductive film, and the conductive layer is cured by the low-temperature curing silver chloride paste, the curing temperature of the low-temperature curing silver chloride paste is ≤90°C, and the curing temperature of the low-temperature curing silver chloride paste is ≤5min.

[0065] This scheme also proposes an application of the above-mentioned silver chloride paste on medical electrode sheets. Since the silver chloride paste can achieve rapid solidification at low temperatures, it can effectively avoid the shrinkage and deformation of the PU conductive film during the preparation of the electrode sheets, thereby further ensuring the conductive performance and service life of the medical electrode sheets.

[0066] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0067] Example 1

[0068] A. Calculated by weight, 5 parts of a base resin and 3 parts of a combined solvent are mixed, and heated and dissolved at 80° C. for 12 hours to obtain a carrier; wherein, calculated by weight, the base resin includes 30 parts of a polyester resin with a glass transition temperature ≥ 70° C., 40 parts of a polyurethane resin with an elongation at break ≥ 700%, and 1 part of an epoxy resin;

[0069] B. Mix a carrier, 40 parts of conductive silver powder and 2 parts of a combined solvent, and stir at 500 rpm for 30 minutes to obtain a pre-made slurry; wherein, calculated by mass, the conductive silver powder includes 40 parts of flaky silver powder with an average flake diameter of 2 to 5 μm, 5 parts of spherical silver powder with a particle diameter of 200 to 500 nm, and 10 parts of silver chloride powder with a particle diameter of 1 to 2 μm; the combined solvent includes a divalent acid ester and methyl isobutyl ketone.

[0070] C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

[0071] Example 2

[0072] A. 15 parts of a base resin and 10 parts of a combined solvent are mixed, and heated and dissolved at 100° C. for 8 hours to obtain a carrier; wherein, the base resin comprises 40 parts of a polyester resin having a glass transition temperature ≥ 70° C., 50 parts of a polyurethane resin having an elongation at break ≥ 700%, and 5 parts of an epoxy resin, calculated by weight;

[0073] B. Mix a carrier, 65 parts of conductive silver powder and 5 parts of a combined solvent, and stir at 250 rpm for 80 minutes to obtain a pre-slurry; wherein, calculated by mass, the conductive silver powder includes 55 parts of flaky silver powder with an average flake diameter of 2 to 5 μm, 10 parts of spherical silver powder with a particle diameter of 200 to 500 nm, and 20 parts of silver chloride powder with a particle diameter of 1 to 2 μm; the combined solvent includes diethylene glycol butyl ether acetate and n-butyl acetate.

[0074] C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

[0075] Example 3

[0076] A. 30 parts of a base resin and 20 parts of a combined solvent are mixed, and heated and dissolved at 120° C. for 6 hours to obtain a carrier; wherein, the base resin comprises 50 parts of a polyester resin having a glass transition temperature ≥ 70° C., 60 parts of a polyurethane resin having an elongation at break ≥ 700%, and 10 parts of an epoxy resin, calculated by weight;

[0077] B. Mix a carrier, 90 parts of conductive silver powder and 10 parts of a combined solvent, and stir at 50 rpm for 120 minutes to obtain a pre-made slurry; wherein, calculated by mass, the conductive silver powder includes 70 parts of flaky silver powder with an average flake diameter of 2 to 5 μm, 20 parts of spherical silver powder with a particle diameter of 200 to 500 nm, and 40 parts of silver chloride powder with a particle diameter of 1 to 2 μm; the combined solvent includes isophorone, diethylene glycol ethyl ether acetate and ethylene glycol ethyl ether acetate.

[0078] C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

[0079] Comparative Example 1

[0080] A. Calculated by weight, 5 parts of a base resin and 3 parts of a combined solvent are mixed, and heated and dissolved at 80° C. for 12 hours to obtain a carrier; wherein, calculated by weight, the base resin includes 70 parts of a polyester resin having a glass transition temperature ≥ 70° C. and 1 part of an epoxy resin;

[0081] B. Mix a carrier, 40 parts of conductive silver powder and 2 parts of a combined solvent, and stir at 500 rpm for 30 minutes to obtain a pre-made slurry; wherein, calculated by mass, the conductive silver powder includes 40 parts of flaky silver powder with an average flake diameter of 2 to 5 μm, 5 parts of spherical silver powder with a particle diameter of 200 to 500 nm, and 10 parts of silver chloride powder with a particle diameter of 1 to 2 μm; the combined solvent includes a divalent acid ester and methyl isobutyl ketone.

[0082] C. Grind the pre-made slurry using a three-roll mill to obtain silver chloride slurry.

[0083] Comparative Example 2

[0084] A. Calculated by weight, 5 parts of a base resin and 3 parts of a combined solvent are mixed, and heated and dissolved at 80° C. for 12 hours to obtain a carrier; wherein, calculated by weight, the base resin includes 70 parts of a polyurethane resin having an elongation at break of ≥700% and 1 part of an epoxy resin;

[0085] B. Mix a carrier, 40 parts of conductive silver powder and 2 parts of a combined solvent, and stir at 500 rpm for 30 minutes to obtain a pre-made slurry; wherein, calculated by mass, the conductive silver powder includes 40 parts of flaky silver powder with an average flake diameter of 2 to 5 μm, 5 parts of spherical silver powder with a particle diameter of 200 to 500 nm, and 10 parts of silver chloride powder with a particle diameter of 1 to 2 μm; the combined solvent includes a divalent acid ester and methyl isobutyl ketone.

[0086] C. Grind the pre-made slurry using a three-roll mill to obtain silver chloride slurry.

[0087] Comparative Example 3

[0088] A. Calculated by weight, 5 parts of a base resin and 3 parts of a combined solvent are mixed, and heated and dissolved at 80° C. for 12 hours to obtain a carrier; wherein, calculated by weight, the base resin includes 30 parts of a polyester resin with a glass transition temperature ≥ 70° C., 40 parts of a polyurethane resin with an elongation at break ≥ 700%, and 1 part of an epoxy resin;

[0089] B. Mix a carrier, 40 parts of conductive silver powder and 2 parts of a combined solvent, and stir at 500 rpm for 30 minutes to obtain a pre-made slurry; wherein, calculated by weight, the conductive silver powder includes 45 parts of flaky silver powder with an average flake diameter of 2 to 5 μm and 10 parts of silver chloride powder with a particle diameter of 1 to 2 μm; and the combined solvent includes a dibasic acid ester and methyl isobutyl ketone.

[0090] C. Grind the pre-made slurry using a three-roll mill to obtain silver chloride slurry.

[0091] Comparative Example 4

[0092] A. Calculated by weight, 5 parts of a base resin and 3 parts of a combined solvent are mixed, and heated and dissolved at 80° C. for 12 hours to obtain a carrier; wherein, calculated by weight, the base resin includes 30 parts of a polyester resin with a glass transition temperature ≥ 70° C., 40 parts of a polyurethane resin with an elongation at break ≥ 700%, and 1 part of an epoxy resin;

[0093] B. Mix a carrier, 40 parts of conductive silver powder and 2 parts of a combined solvent, and stir at 500 rpm for 30 minutes to obtain a pre-made slurry; wherein, calculated by weight, the conductive silver powder includes 45 parts of spherical silver powder with a particle size of 200 to 500 nm and 10 parts of silver chloride powder with a particle size of 1 to 2 μm; and the combined solvent includes a divalent acid ester and methyl isobutyl ketone.

[0094] C. Grind the pre-made slurry using a three-roll mill to obtain silver chloride slurry.

[0095] The silver chloride pastes of Examples 1-3, Comparative Examples 1-4, and conventional silver chloride pastes in the prior art were respectively printed on the top of the PU conductive film by screen printing to obtain samples, and the printing thickness of the silver chloride paste was 10 μm; the samples were dried in a drying oven at a temperature of 90° C., and the drying time was 5 minutes. The surface effects of the samples were observed, and conventional tests in the field of conductive paste were performed on them, and the results are shown in Table 1 below.

[0096] Table 1 Test results of samples of Examples 1-3 and Comparative Examples 1-4

[0097]

[0098] From the test results of sample performance in Table 1, it can be seen that the silver chloride paste prepared by this scheme can be quickly cured at a low temperature of 90°C, and the surface square resistance, adhesion, hardness, flexibility and aging resistance of the sample after curing all meet the use requirements.

[0099] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A medical electrode sheet, characterized in that: It comprises a PU conductive film and a conductive layer, wherein the conductive layer is arranged on the top of the PU conductive film, and the conductive layer is cured by low-temperature curing silver chloride paste, the curing temperature of the low-temperature curing silver chloride paste is ≤90°C, and the curing time of the low-temperature curing silver chloride paste is ≤5min; Calculated by weight, the low-temperature curing silver chloride paste includes 5 to 30 parts of base resin, 40 to 90 parts of conductive silver powder and 5 to 30 parts of combined solvent; The matrix resin includes polyester resin, polyurethane resin and epoxy resin; The conductive silver powder includes flaky silver powder, spherical silver powder and silver chloride powder, the average flake diameter of the flaky silver powder is 2-5 μm, and the particle diameter of the spherical silver powder is 200-500 nm; The combined solvent includes a first solvent and a second solvent, the boiling point of the first solvent is ≥180°C, the boiling point of the second solvent is ≥100°C, and the boiling point of the second solvent is <180°C; Calculated by weight, the matrix resin includes 30 to 50 parts of polyester resin, 40 to 60 parts of polyurethane resin and 1 to 10 parts of epoxy resin; The glass transition temperature of the polyester resin is ≥70°C; The first solvent includes any one or more combinations of dibasic acid esters, diethylene glycol butyl ether acetate, isophorone and diethylene glycol ethyl ether acetate; The second solvent includes any one or more combinations of methyl isobutyl ketone, n-butyl acetate and ethylene glycol ethyl ether acetate.

2. A medical electrode sheet according to claim 1, characterized in that: The elongation at break of the polyurethane resin is ≥700%.

3. The medical electrode sheet according to claim 1, characterized in that: Calculated by weight, the conductive silver powder includes 40 to 70 parts of flaky silver powder, 5 to 20 parts of spherical silver powder and 10 to 40 parts of silver chloride powder.

4. The medical electrode sheet according to claim 1, characterized in that: The particle size of the silver chloride powder is 1-2 μm.

5. The medical electrode sheet according to claim 1, characterized in that: The preparation method of the low-temperature curing silver chloride paste comprises the following steps: A. Mixing a formulated amount of base resin and a part of a formulated amount of a combined solvent, heating and dissolving, to obtain a carrier; B. Mixing the carrier, the formulated amount of conductive silver powder and the remaining formulated amount of the combined solvent, and stirring at a low speed to obtain a pre-made slurry; C. Grind the pre-made slurry using a three-roll grinder to obtain a low-temperature curing silver chloride slurry.

6. The medical electrode sheet according to claim 5, characterized in that: In step A, the dissolution temperature of the heating and dissolving step is 80 to 120° C., and the dissolution time is 6 to 12 hours; In step B, the stirring speed of the low-speed stirring step is 50 to 500 rpm, and the stirring time is 30 to 120 min.

Citation Information

Patent Citations

  • Conductive ink for transfer printing process and preparation method thereof

    CN113527948A

  • Silver-silver chloride paste for flexible electrocardiogram detection electrode and application of silver-silver chloride paste

    CN114334218A